Contribution of Increased Expression of Yin Yang 2 to Development of Cardiomyopathy - Zhang, Yi; Beketaev, Ilimbek; Segura, Ana Maria; Yu, Wei; Xi, Yutao; Chang, Jiang; Ma, Yanlin; Wang, Jun (Frontiers in Molecular Biosciences, 2020)
Yin Yang 2 (YY2) is a member of the Yin Yang family of transcription factors. Although the bioactivity of YY2 has been previously studied, its role in cardiovascular diseases is not known. We observed the increased expression of YY2 in failing human hearts compared with control hearts, raising the question of whether YY2 is involved in the pathogenesis of cardiomyopathy. To investigate the potential contribution of YY2 to the development of cardiomyopathy, we crossed two transgenic (Tg) mouse lines, pCAG-YY2-Tg+ and -MHC-Cre, to generate two independent double transgenic (dTg) mouse lines in which the conditional cardiomyocyte-specific expression of YY2 driven by the -MHC promoter was mediated by Cre recombinase, starting at embryonic day 9.0. In dTg mice, we observed partial embryonic lethality and hearts with defective cardiomyocyte proliferation. Surviving dTg mice from both lines developed cardiomyopathy and heart failure that occurred with aging, showing different degrees of severity that were associated with the level of transgene expression. The development of cardiomyopathy was accompanied by increased levels of cardiac disease markers, apoptosis, and cardiac fibrosis. Our studies further revealed that the Cre-mediated cardiomyocyte-specific increase in YY2 expression led to increased levels of Beclin 1 and LC3II, indicating that YY2 is involved in mediating autophagic activity in mouse hearts in vivo. Also, compared with control hearts, dTG mouse hearts showed increased JNK activity. Because autophagy and JNK activity are important for maintaining cardiac homeostasis, the dysregulation of these signaling pathways may contribute to YY2-induced cardiomyopathy and heart failure in vivo.